RANCANGAN APLIKASI DISTRIBUSI MAKANAN RINGAN DENGAN PENDEKATAN CUSTOMER RELATIONSHIP MANAGEMENT DAN METODE RAD - Edy Nasri; Kornelis Kornelis; Dikri Muhammad Fauzi (LPPM Unbaja, 2022)
Sky Putra Pancasurya is a company engaged in the sale of secondary needs, the company markets products that have been obtained through a marketing team. Because in the distribution of its products still using a conventional system found several problems that often occur, one of which is misinformation of goods between customers and companies, therefore an application is expected to make it easier for customers to buy the products they need, and certainly make it easier for companies to transact with its customers. Making this application begins by analyzing existing systems in the company. Then UML is made as a system modeling tool. Rapid Application Development (RAD) as the method and Customer Relationship Management (CRM) for its approach, for Payment gateway using Midtrans. Continued by making an interface design and creating the program. This application was created using the PHP programming language, MySQL as a database, Laravel Framework as a framework and Visual Studio Code as the text editor. This application has two main functions, namely for buyers who can view the product catalog and buy products and admin to manage users, products and transactions.